Changes in preoperative characteristics in patients undergoing radical prostatectomy – a 16-year nationwide analysis. (March 2014) - Røder, Martin Andreas; Brasso, Klaus; Christensen, Ib Jarle; Johansen, Jørgen; Langkilde, Niels Christian; Hvarness, Helle; Carlsson, Steen; Jakobsen, Henrik; Borre, Michael; Iversen, Peter
Abstract Background. The Danish attitude for diagnosis and treatment of early localized prostate cancer (PCa) has historically been conservative. Denmark introduced radical prostatectomy (RP) as the last of the Nordic countries in 1995. However, a rapid increment in the Danish incidence of PCa is indicative of a shift in attitude with increasing opportunistic PSA testing. This had led to an increasing number of RPs being performed in Denmark. The objective of this study was to analyze changes in preoperative characteristics over time for the complete cohort of 6489 men who underwent RP between 1995 and 2011. Our hypothesis was that an increasing amount of men undergo RP for lower risk PCa. Material and methods. All patients operated from 1995 to 2011 were identified via patient files and registries. Changes over time in age at surgery, preoperative PSA, clinical T-category, biopsy Gleason score (GS), and D'Amico classification are described. Tests for statistically significant changes were performed. Results. Median age increased from 61.4 to 64.8 years (p < 0.0001) during the 16-year period. Median PSA declined from 11.5 to 7.9 ng/ml (p < 0.0001). Distribution of biopsy GS changed significantly, especially after 2005. Biopsy GS = 7 was found in 20.2% of the patients in 2005 compared to 57.1% in 2011. The proportion of T1 disease increased from 32% to 56%. Significant changes in percentage of patients according to the D'Amico classification were found. After 2005 the proportion of intermediate-risk patients increased significantly. The proportion of patients age 70 or above increased from 2% to 13% in the period studies. Conclusion. Significant preoperative stage- and Gleason grade migration was found in this complete Danish nationwide cohort of patients undergoing RP during the past 16 years. This effect is most likely attributed to an increasing use of PSA as marker for early prostate cancer diagnosis in Denmark and new international guidelines for Gleason grading and scoring.